Kompetensi Guru Pendidikan Agama Islam dalam Meningkatkan Potensi Peserta Didik di SMK Islam Al-Irsyad Kebon Kongok Suka Makmur Lombok Barat Provinsi Nusa Tenggara Barat - Mastur (Jurnal LENTERA: Jurnal Studi Pendidikan, 2021)
The purpose of this study is to determine 1). Competence of Islamic Religious Education Teachers in teaching and learning activities at Islamic Vocational High School Al-Irsyad Kebon Kongok, 2). The application of the competence of Islamic religious education teachers in improving student achievement of Islamic Vocational High School Al-Irsyad Kebon Kongok. The research method used in this research is qualitative. This means that the resulting data is descriptive, where the researcher does not only collect and compile data but analyzes and interprets it. The data analysis used is inductive descriptive analysis, namely analysis by describing specific events or data to conclude into a general conclusion. Based on the results of the data analysis carried out, the following data were obtained, namely the learning outcomes of students in the field of Islamic Religious Education the average score was 71.63, the learning outcomes of the students in the field of study aqidah morals the average score was 71.10, then the learning outcomes of students in the field of Islamic religious education, the average was 75.33, and the English learning outcome score was 70.78. By looking at these results we can say that the competence possessed by the Islamic Religious Education teacher at the Islamic Vocational School Al-Irsyad Kebon Kongok Suka Makmur, Gerung District, West Lombok, West Nusa Tenggara Province is sufficient to improve student learning achievement because the results obtained have met the completeness standards. minimal